Oligoether Ester-Functionalized ProDOT Copolymers on Si/Monolayer Graphene as Capacitive Thin Film Electrodes. Issue 7 (23rd March 2020) - Karazehir, Tolga; Sarac, Baran; Gilsing, Hans-Detlev; Eckert, Jürgen; Sarac, A. Sezai
Abstract : In this study, electrochemical polymerization of 3, 4-propylenedioxythiophene (ProDOT 1), ProDOT bearing oligoether ester (ProDOT-EO-ester 2 ) and their copolymerization onto homogeneously CVD coated nano-graphene/Si support is realized to attain graphene/ProDOT based copolymer hybrid nanostructures. By introducing oligoether side chain to ProDOT backbone and using different [ProDOT]/[ProDOT-EO-ester] molar ratios ensures a considerable decrease in oxidation potential of polymer allowing tunable properties to copolymers revealing improvement electrochemical capacitance and electrochemical activity which are clearly reflected by the experimental results. Capacitive behavior of copolymers is determined by electrochemical impedance spectroscopy, cyclic voltammetry. Moreover, The structural, morphological and spectroscopic characterization of the copolymers is investigated by XRD, AFM, SEM, EDX, FTIR, and Raman, respectively. By the increase of ProDOT in the copolymer composition, the higher dopant concentration is attained suggesting an enhanced conductivity agree well with the impedance and CV results, where the copolymerization of ProDOT 1 and ProDOT-EO-ester 2 in equal molarity results in the highest specific capacitance and redox activity. The adopted equivalent circuit model for polymers is in good agreement with the experimental data of impedance. Due to the difference in conjugated structure between ProDOT and ProDOT-EO-ester by the presence of the EO-ester group leads to a decrease in charge transfer resistance with increasing mole fraction of ProDOT-EO-ester. The charge transfer resistance of [ProDOT]0 /[ProDOT-EO-ester]0 = 1:1 coated Si/graphene is nearly 51 and 24 times lower value compared to those of PProDOT and P(ProDOT-EO-ester) homopolymers coated Si/graphene, respectively, confirming that the copolymerization improves the electron conduction. By Mott-Schottky measurements, increasing mole fraction of ProDOT-EO-ester 2 in copolymer composition results in the alteration of semiconducting behavior. The developed graphene-polymer hybrid electrodes can be a potential candidate for energy storage devices.